Māori Academic Challenges: Delivering Mātauranga Māori During COVID-19 - Te Momo, Fiona (Journal of Contemporary Issues in Education, 2022)
In March 2020, the COVID-19 pandemic disrupted academic educational programmes in universities across the world, including Aotearoa New Zealand. For Māori academics who implement mātauranga Māori as a pedagogy, it became theoretically and practically challenging teaching virtually and online. The Te Taha Tinana, of Te Whare Tapa Wha model, created by aDurie in 1984 (Health Navigator, 2022) regarding the four dimensions of well-being, focuses on the physical presence, physical embodiment, and physical behaviour. This could not be easily taught virtuality through a computer screen during COVID-19 lockdown. For Māori academics transitioning from teaching Mātauranga Māori in person to an online environment brought forth these challenges. The challenges re-emerged in August 2021 when New Zealand went into Level 4 lockdown overnight because of the new COVID-19 Delta Virus variant. In 2022, the Omicron variant caused many universities in Aotearoa New Zealand to continue their first semester teaching online. Mātauranga Māori is a body of knowledge exercised by Māori people in New Zealand. Sadler (2007) argues Mātauranga Māori was first invented by Māori when Pākehā (English people) arrived in New Zealand. He suggests Mātauranga Māori is a paradigm where Māori define the parameters. Royal (2009; 2012) claims this knowledge was brought to New Zealand by Polynesian ancestors and is an evolutionary continuum of knowledge that relates to encountering the world as Māori with the focus on improving humankind. Le Grice, Braun, and Wetherell (2017) state Mātauranga Māori incorporates theories, practices, and protocols that are bound to relationships, people, and places in a world that supports Māori ambitions. This knowledge, for me an Indigenous Māori academic, incorporates the physical and spiritual worlds embracing the energies of the universe handed down by our forefathers. This position paper discusses the pedagogical challenges encountered during COVID-19 Lockdown for Indigenous academics to continue delivering programmes requiring indigenous expertise and human contact. It explores: 1) the Covid 19 Educational Barriers; 2) Online Academic Challenges; 3) Managing Cultural Shifts; 4) Sustaining Indigenous Pedagogy. It asserts that Mātauranga Māori contributes to the growth of Indigenous knowledge on a world stage and the challenges indigenous academics encounter brought by a global pandemic.